THE CORRELATION BETWEEN FAMILY SUPPORT AND RELAPSE IN SCHIZOPHRENIA AT THE PSYCHIATRIC HOSPITAL - Rostime Hermayerni Simanullang (Belitung Raya Foundation, 2018)
Background: Schizophrenia is a severe mental illness with the majority of patients' experiences relapses. Family support is not a new topic, but still considered as an important factor to prevent the relapse. However, little is known about the correlation between family support and relapse in schizophrenia patients in North Sumatra, Indonesia. Objective: This study aims to examine the relationship between family support and relapse in schizophrenia. Methods: This was a correlational cross sectional study conducted from January to May 2015 at the psychiatric hospital in Medan North Sumatra Indonesia. There were 90 samples selected using purposive sampling. Chi Square test was used to analyze the data. Results: Findings of this study reveals that there was statistically significant relationship between family informational support (p=0.00), appraisal support (p=0.00), instrumental support (p=0.00), and emotional support (p=0.00) with relapse in schizophrenia. Conclusion: There is a significant correlation between family support (informational support, appraisal, instrumental and emotional support) and relapse in schizophrenia. Therefore, it is recommended that health care professional should continuously promote the important of family support and increase their knowledge regarding the type of supports needed for patients with schizophrenia.